1967
DOI: 10.1210/endo-81-2-306
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Hypocalcemic Activity of Porcine Thyrocalcitonin

Abstract: Porcine thyrocalcitonin was modified by enzymatic and chemical treatment for the purpose of studying the interrelationships between structure and hypocalcemic activity. Enzymatic treatment with trypsin, chymotrypsin, pepsin and polyphenyl oxidase led to rapid and complete inactivation of the hypocalcemic activity. We conclude from these experiments that thyrocalcitonin either is a simple polypeptide or contains a peptide moiety which is absolutely essential for hypocalcemic activity. Incubation of thyrocalcito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1967
1967
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…These characteristics of the -175-unpurified hypocalcemic principle in the microsomal fraction are in accordance with the findings of Tashjian and Warnock (1967) in their studies with crude extracts of porcine CT.…”
Section: Incorporation Of Glycine-c-14 Into These Fractionssupporting
confidence: 89%
See 2 more Smart Citations
“…These characteristics of the -175-unpurified hypocalcemic principle in the microsomal fraction are in accordance with the findings of Tashjian and Warnock (1967) in their studies with crude extracts of porcine CT.…”
Section: Incorporation Of Glycine-c-14 Into These Fractionssupporting
confidence: 89%
“…Baghdiantz et al (1964), Hirsch et al (1964), and Tashjian and Warnock (1967) also demonstrated the peptide nature and the purconcomitant loss of biological activity of their relatively impure -CT preparations. These hypocalcemic preparations were readily in-.activated by incubating them with a variety of proteolytic enzymes such as trypsin and pepsin.…”
Section: Biologicai Assay and Radioimmunoassay Biological Ass~ymentioning
confidence: 93%
See 1 more Smart Citation
“…It was shown that the hypocalcaemic activity was relatively stable to heat at neutral and acid pH. This has been reported to be a property of crude porcine calcitonin preparations (Tashjian & Warnock, 1967;Aldred & Schlueter, 1969). Pure preparations of porcine calcitonin are completely inactivated in vitro after incubation at 37°C in 0-1 M-tris (pH 7-5) for 4 h. Like the crude preparation of the hormone, the grey-lethal mouse plasma may contain some material which protects the calcium-lowering factor from inactivation.…”
Section: Discussionmentioning
confidence: 93%